Economic outlook for Southeast Asia, China and India 2018 fostering growth through digitalisation. - Organisation for Economic Co-operation and Development; Organisation for Economic Co-operation and Development. Development Centre ([Paris] OECD Publishing, 2018)
"The Economic Outlook for Southeast Asia, China and India is a bi-annual publication on regional economic growth, development and regional integration in Emerging Asia. It focuses on the economic conditions of Association of Southeast Asian Nations (ASEAN) member countries: Brunei Darussalam, Cambodia, Indonesia, Lao PDR, Malaysia, Myanmar, the Philippines, Singapore, Thailand and Viet Nam. It also addresses relevant economic issues in China and India to fully reflect economic developments in the region. Each edition of the Outlook comprises four main parts, each highlighting a particular dimension of recent economic developments in the region. The first part presents the regional economic monitor, depicting the economic outlook and macroeconomic challenges in the region. The second part takes stock of recent progress made in key aspects of regional integration. The third part consists of a special thematic chapter addressing a major issue facing the region. The 2018 edition focuses on fostering growth through digitalisation. And the fourth part includes structural policy country notes offering country-specific reviews and recommendations."--Provided by publisher.
Presents the economic conditions of each ASEAN country and two large economies in the region, China and India. Deals with four main topics on the regional economic outlook to 2022, recent development in regional integration, the impacts of digitalization on manufacturing and services in the region, and country notes on key structural policy challenges.
Keywords: Southeast Asia -- Economic conditions -- 21st century; China -- Economic conditions -- 2000.; India -- Economic conditions -- 1991.; Southeast Asia -- Economic policy -- Periodicals